Kenya. - Dorling Kindersley Limited (London ; New York : DK / Dorling Kindersley Ltd., 2009)
"Wildlife, national parks, tribal culture, beaches, driving, hiking, safaris, maps, game lodges, restaurants, habitats."
Includes index.
Colored maps on lining papers.
Issue for 2009- also called 1st American ed.
Keywords: Kenya; Kenya; Guidebooks; Description and travel